Association of a low vitamin D status with risk of post-stroke depression: A meta-analysis and systematic review - Hung, Kuo-Chuan; Wu, Jheng-Yan; Illias, Amina M.; Chiu, Chong-Chi; Chang, Ying-Jen; Liao, Shu-Wei; Wang, Kuei-Fen; Chen, I-Wen; Sun, Cheuk-Kwan (Frontiers in Nutrition, 2023)
Background: Although post-stroke depression (PSD) affects one-third of patients following an acute stroke, pooled evidence addressing the correlation between a low vitamin D status and the risk of PSD remains inconclusive. Methods: Comprehensive database search of Medline, EMBASE, Cochrane library, and Google Scholar was performed from inception to December 2022. The primary outcome was the association of PSD risk with a low vitamin D status, while the secondary outcomes included the relationship between PSD and other risk factors. Results: Analysis of seven observational studies published between 2014 and 2022 with 1580 patients showed pooled incidences of vitamin D deficiency (defined as 25[OH] D levels <50 nmol/L) and PSD of 60.1% and 26.1%, respectively. Patients with PSD had a lower circulating vitamin D concentration compared to those without [mean difference (MD)=-13.94 nmol/L, 95% CI: -21.83 to -6.05, p=0.0005, I2=91%, six studies, 1414 patients]. Meta-analysis also demonstrated a correlation between a low vitamin D level and an increased PSD risk [odd ratio (OR)=3.25, 95% CI: 1.57 to 6.69, p=0.001, I2=78.7%,1108 patients], the heterogeneity of which was found to be associated with the incidence of vitamin D deficiency but not female proportion on meta-regression. Besides, female gender (OR=1.78, 95% CI: 1.3 to 2.44, p=0.003, I2=31%, five studies, 1220 patients), hyperlipidemia (OR=1.55, 95% CI: 1.01 to 2.36, p=0.04, I2=0%, four studies, 976 patients), and high National Institutes of Health Stroke Scale (NIHSS) scores (MD=1.45, 95% CI: 0.58 to 2.32, p=0.001, I2=82%, five studies, 1220 patients) were potential risk factors for PSD. For the primary outcome, the certainty of evidence was very low. Regarding secondary outcomes, the certainty of evidence was low for BMI, female gender, hypertension, diabetes, and stroke history, and very low for age, level of education, hyperlipidemia, cardiovascular disease, and NIHSS scores. Conclusion: The results suggested an association of a low circulating vitamin D level with an increased risk of PSD. Besides, female gender, hyperlipidemia, high NIHSS score were related to an increased risk or occurrence of PSD. The current study may imply the necessity of routine circulating vitamin D screening in this population.